1989
DOI: 10.1210/mend-3-3-518
|View full text |Cite
|
Sign up to set email alerts
|

Rat Parathyroid Hormone-Like Peptide: Comparison with the Human Homologue and Expression in Malignant and Normal Tissue

Abstract: A rat Leydig cell tumor cDNA library was screened with a 32P-labeled genomic restriction fragment encoding human PTH-like peptide (hPLP), and three cDNA clones were isolated. The largest cDNA insert contained 1146 nucleotides. The cloned cDNA encodes a 177-amino acid protein consisting of a predicted 36-amino acid leader sequence and a 141-amino acid mature peptide in which 9 of 13 amino-terminal residues are identical to rat PTH (rPTH). Comparison of rPLP with hPLP reveals marked conservation of both the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…Plasmid Construction-All PTHrP constructs were derived from the cDNA encoding rat prepro-PTHrP (PLPm10) (25). For transfection studies, prepro-PTHrP was expressed with a histidine tag at the COOH terminus using the mammalian expression vector pRC/CMV (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid Construction-All PTHrP constructs were derived from the cDNA encoding rat prepro-PTHrP (PLPm10) (25). For transfection studies, prepro-PTHrP was expressed with a histidine tag at the COOH terminus using the mammalian expression vector pRC/CMV (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse FGF-R1 [ (Mansukhani et al, 1990) a gift of C. Basilico, New York, NY] was a 400 bp cDNA HincII-PstI fragment. Rat PTHrP [ (Yasuda et al, 1989) …”
Section: Southern Blots and Hybridizationmentioning
confidence: 99%
“…87:884-893.) Key words: calcium * epidermal growth factorkeratinocyte differentiation * transient transfection Messenger RNAs and the gene encoding parathyroid hormone (PTH)-like peptide (PLP),' which was initially isolated from human tumors associated with hypercalcemia (1-3), have now been cloned and characterized in the human (4-9) and rat (10)(11)(12). PLP mimics many of the biological actions of PTH (13), but is also likely to have its own functions which are separate from its PTH-like effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, multiple PLP transcripts may not al- Our transient transfection analysis demonstrated that both GF and serum enhanced PLP promoter activity indicating that at least part of the stimulatory effect of these modulators on PLP production in keratinocytes resides at the level of augmenting gene expression. The difference in the apparent kinetics of the effect of growth factors and serum on enhancing endogenous PLP production by keratinocytes and on increasing hGH release during transient transfection assays may re- (11).…”
Section: Introductionmentioning
confidence: 99%